Oles Honchar's Individual Author's Word Formation Model: Parts-of-Speech Aspect (Linguostylistic Studies, 2018)
The individual language style of a writer is first of all the author's choice, creative use of those resources of the native language, which correspond to the constants of his world outlook in the best way. The purpose of the research is to trace the relationship between Oles Honchar’s worldview and his individually outlined linguistic means of constructing new words/lexemes. The case study is based on the Oles Honchar's artistic texts. The method of contextual analysis is used to clarify the semantic structure of new words and comparative analysis – to reveal productive tokens of different part-of-speech word classes. The key findings of the study argue that Oles Honchar's most productive model is noun-word formation, which serves as a means of portraying characters. The most frequent are suffix-based formations. Quite often, the writer refers to the creation of collective nouns. The word-formation models, based on typical national models, can be considered as individually pronounced ones. Some occasionalisms have a clear folk or colloquial basis. In the prefix-based word formation pattern, there is a tendency to use the prefixes anti-, over-, pseudo-. Adjective word formation testified to the use of productive in the Ukrainian language suffixes -ast-, -ist-, -ovit-. Complex adjectives in Oles Honchar's linguistic innovations are not frequent. The study has also revealed that verb word formation can is unproductive. In most cases, adjectives of quality are the basis for the creation of occasional adverbs. Oles Honchar’s novelties convincingly prove that individual author's word formation models are an integral feature of his style and vision of the world. We see the prospect for further studies in comparing the register of the analyzed occasionalisms with the word usage tendencies of other authors.
Keywords: individual author’s word-formation model; novelty; neologism; conceptual significance